BIM in small-scale sustainable design - Levy, Francois, 1966- (Hoboken, NJ : Wiley, 2012)
'While most books related to BIM are focused on large-scale architectural projects, this is the only book focused on BIM strategies for modest-scaled architectural projects that are sustainably designed. Specific in its examples and methods, the book serves as practical guide for architects and is intended to be a desktop companion. Other books, other than software guides, tend to treat BIM or sustainable practices separately in a high-level discussion'--Provided by publisher.
'This book focuses on BIM strategies for modest-scaled architectural projects that are sustainably designed. Specific in its examples and methods, the book serves as practical guide for architects and is intended to be a desktop companion. Other books, other than software guides, tend to treat BIM or sustainable practices separately in a high-level discussion'--Provided by publisher.
Cover; Contents; Title; Copyright; Acknowledgments; Introduction; Building Information Models and Modeling; The cost of buildings; See, change; BIM for the rest of us; What this book is, and isn't; A word on the case studies; Chapter 1: BIM and Sustainable Design; The emergence of Building Information Modeling; BIM for design; High-performance architecture; Chapter 2: Design Software; BIM applications; Complementary software; Further reading; Chapter 3: Site Analysis; Developing a site model; Analyzing the site; Chapter 4: Massing Analysis; Creating massing models.
Includes bibliographical references (pages 279-281) and index.
Keywords: Building information modeling; Sustainable construction; TECHNOLOGY & ENGINEERING -- Environmental -- General; Building information modeling; Sustainable construction; Bauentwurf; Bauplanung; Building Information Modeling; Computersimulation; Datenverarbeitung; Nachhaltigkeit; Bauentwurf; Datenverarbeitung; Computersimulation; Bauplanung; Nachhaltigkeit; Electronic book; Electronic books